The effect of periodontal therapy on neopterin and vascular cell adhesion molecule-1 levels in chronic periodontitis patients with and without acute myocardial infarction: a case-control study - Zeynep Turgut Çankaya; Ayşen Bodur; Gülten Taçoy; Imge Ergüder; Derya Aktuna; Atiye Çengel (University of São Paulo, 2018)
Abstract The presence of neopterin in gingival crevicular fluid (GCF) is a marker for local and acute immune activation, and the presence of vascular cell adhesion molecule (VCAM-1) in GCF is accepted as a marker for chronic vascular inflammation. Objectives This study aimed to evaluate effects of periodontal treatment on GCF levels of neopterin and VCAM-1 in patients with chronic periodontitis (CP) with acute myocardial infarction (AMI) compared with systemically healthy CP patients. Material and methods Sixty subjects (20 CP patients with AMI, 20 healthy CP patients, and 20 healthy controls) were included. GCF samples were analyzed at baseline and after 3 and 6 months, and the probing pocket depth (PD), clinical attachment level (CAL), bleeding on probing, gingival (GI) and plaque (PI) indices were recorded. We determined neopterin and VCAM-1 levels (concentration and total amount) using enzyme-linked immunosorbent assay (ELISA). No significant differences were seen between the AMI+CP and CP groups for PI, GI, GCF levels of neopterin and VCAM-1 at baseline. Results The number of teeth with 5 mm≤CAL<7 mm and CAL≥7 mm were significantly increased in the AMI+CP group at baseline. There were no significant differences between the AMI+CP and CP for PI, CAL, GCF volumes, and the AMI+CP group had the highest clinical improvement in the number of teeth with 5 mm≤CAL<7 mm at the sixth month. There were significant positive correlations between clinical periodontal inflammation and the presence of neopterin and VCAM-1 in GCF prior to and following periodontal treatment, and between the GCF volume and clinical parameters. Conclusions Data suggest that the total amount and concentration of neopterin and VCAM-1 in GCF seemed to be closely associated with periodontal disease severity in CP patients with AMI. Moreover, the results of our study demonstrate that the past periodontal status is potentially correlated between groups, with similar periodontal disease severity.